Analisis kemampuan pemahaman konsep matematis siswa yang memiliki gaya belajar visual berdasarkan Teori Skemp - Dewi Wulansari; Yuyu Yuhana; Abdul Fatah (TIRTAMATH: Jurnal Penelitian dan Pengajaran Matematika, 2022)
Concept understanding is a basic understanding that must be possessed by students before solving a mathematical problem. The inability of students to understand well can be caused by several factors, one of which is learning style. There are three kinds of learning styles, namely visual, auditory and kinesthetic. The purpose of this study is to analyze and describe the ability to understand mathematical concepts of students who have a visual learning style based on the Skemp’s theory. This study uses descriptive qualitative research methods. Data collection techniques were carried out by providing learning style questionnaires, instruments for understanding mathematical concepts, and interviews. The research subjects were students of class X Tata Boga at one of the State Vocational Schools of Serang City who had a visual learning style of 17 people with 5 students who were taken as research subjects. The results showed that subjects with the visual learning style category had different ability to understand mathematical concepts, from 17 students who had visual learning styles, 23% were in the relational understanding category, 59% were in the instrumental understanding category, and 18% did not in any category or can be categorized as not understanding the concept.